Leveraging opportunities for self-regulated learning in smart learning environments - Idit Adler; Scott Warren; Cathleen Norris; Elliot Soloway (Smart Learning Environments, 2025)
Abstract Smart learning environments provide students with opportunities to engage in self-regulated learning (SRL). However, little research has examined how teachers leverage these opportunities. We employed a multiple-case study methodology to examine the SRL supporting instructional practices of five third-grade teachers as they implemented a science unit embedded within a smart learning environment which enabled student engagement in SRL processes. The identified set of instructional practices was used to formulate the teachers’ SRL support profiles, which indicates the extent to which teachers provided students with opportunities to regulate the cognitive aspect of SRL. Our findings indicated that teachers’ interactions with the smart learning environment varied from teacher-focused use, restricting opportunities for SRL engagement, to student-focused use, leveraging opportunities for student engagement in SRL. These results demonstrate that, while smart learning environments potentially provide rich contexts for students’ engagement in SRL, how teachers use this environment through their SRL-supporting instructional practices determines students’ actual engagement in SRL.